Costa Rica : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report provides a summary of Costa Rica's macroeconomic data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS), together with a summary assessment of the dimensions of data quality underlying national accounts statistics, consumer and producer price statistics, government finance statistics, monetary statistics, and balance-of-payments statistics. The authorities are in observance of nearly all SDDS specifications used by the IMF to determine observance of the Standard-that is, coverage, periodicity, and timeliness of the data and the dissemination of advance release calendars. In some instances, timeliness exceeds SDDS requirements.